Analisis Semiotika Pada Film Series Gadis Kretek Terhadap Representasi Gender - Azura, Sylvia; Rohani, Laila (Asosiasi Ide Bahasa Kepri, 2024)
Currently, there are still many Indonesian people who apply patriarchal culture, so this can be used as the main topic for making literary works such as films. The researcher decided to make the Film Series